Electrically tunable and broader-band sound absorption by using micro-perforated dielectric elastomer actuator - Lu, Zhenbo (2017)
Most membrane-type acoustic absorbers for low-frequency sound attenuation are applicable only at a fixed resonant frequency for a narrow bandwidth. Tuning of the acoustic absorption spectrum is desired to match the varying noises. This letter presents a micro-perforated dielectric elastomer actuator (MPDEA) to make a broader-band acoustic absorber electrically tunable. Voltage activation of the MPDEA reduces the membrane tension and hole size and thus enables the active shifting of the acoustic absorption spectrum. Such a membrane tuning method does not require discrete mechanical parts as for the cavity tuning method. Also presented are the analytical models to predict the voltage-induced hole size change and acoustic characteristics of MPDEA.